Assessing wild bee fauna (Hymenoptera: Apoidea: Anthophila) in Calabria (southern Italy) - M. L. Vommaro; M. Lento; D. Michez; S. Flaminio; S. Flori; I. Treccosti; G. Di Prisco; L. Goglia; P. Brandmayr; A. Giglio (The European Zoological Journal, 2025)
The ecological importance of wild bees as pollinators has become more widely recognized in recent years. However, knowledge regarding their diversity and distribution in numerous regions of Italy remains deficient in comparison to other Mediterranean countries. This study, conducted over a three-year period (2022–2024), surveyed eight sites in an area designated as a UNESCO (United Nations Educational, Scientific and Cultural Organization) Man and Biosphere Reserve in Calabria. The sampling methods included transect walks and pan traps, leading to the identification of 80 species, classified into 17 genera belonging to four families (Andrenidae, Apidae, Halictidae, Megachilidae). Among them, 16 species were documented for the first time in Calabria, i.e. A. binominata, A.cineraria, A. fumida, A. gravida, A. haemorrhoa, A. lathyri, A. pandellei, A. polita (Andrenidae); Lasioglossum aeratum, L. transitorium, L. xanthopus, Sphecodes spinulosus (Halictidae); Hoplitis cristatula, Osmialigurica, O. scutellaris (Megachilidae) and Eucera nigrifacies (Apidae). The study also documented bee–flora interactions, noting 40 plant genera from 21 families. New insights into the dietary preferences of Seladonia seladonia and Andrena fumida were obtained, alongside novel plant associations for several oligolectic species (A. pandellei, A. agilissima, A. humilis, A. lagopus, A. russula, L. brevicorne, H. cristatula, O. leaiana). These findings contribute to the knowledge about the distribution and ecology of the bee fauna in southern Italy, in particular, and in Europe in general.